Griffiths Scales of Child Development 3rd Edition: normalization for the Brazilian population - Ferreira-Vasques, Amanda Tragueta; da Rocha, Eduardo Pimentel; Green, Elizabeth; Lamônica, Dionísia Aparecida Cusin (Frontiers in Pediatrics, 2025)
IntroductionChild development must be carefully evaluated, requiring assessment instruments to assess different areas of development. Griffiths Scales of Child Development 3rd Edition (Griffiths III) is used to assess different areas of development in children. This study normalized Griffiths III for the Brazilian population from 0 to 72 months.Methods445 typically developing children from 0 to 72 months, divided into eight groups (from 0 to 6 months; 7 to 12 months; 13 to 18 months; 19 to 24 months; 25 to 36 months; 37 to 48 months; 49 to 60 months; 61 to 72 months) participated. Their tutors answered the anamnesis protocol. Denver II Developmental Screening Test and Griffiths III were applied. Statistical analysis was performed using the Mann–Whitney Test and Spearman's rank correlation coefficient. Normalization followed the criteria of the original scale.ResultsThere was a direct and statistically significant correlation between maternal schooling and socioeconomic status; a direct correlation in the performance between the subscales. The normalization table of Griffiths III with the developmental age of children from 0 to 72 months was elaborated through linear progression, calculated using a specific formula.DiscussionThe data collected for the Brazilian population from 0 to 72 months were normalized, following the guidelines and norms of the original Griffiths III.